Association between common polymorphisms of the proopiomelanocortin gene and body fat distribution: a family study. - Baker, M; Gaukrodger, N; Mayosi, B; Imrie, H; Farrall, M; Watkins, H; Connell, J; Avery, P; Keavney, B (2005)
Rare mutations in the proopiomelanocortin (POMC) gene cause severe early-onset childhood obesity. However, it is unknown whether common variants in POMC are responsible for variation in body weight or fat distribution within the commonly observed range in the population. We tested for association between three polymorphisms spanning the POMC gene and obesity phenotypes in 1,428 members of 248 families. There was significant association between genotypes at the C8246T (P < 0.0001) and C1032G (P = 0.003) polymorphisms and waist-to-hip ratio (WHR) corrected for age, sex, smoking, exercise, and alcohol consumption. Each T allele at C8246T (or G allele at C1032G) was associated with a 0.2-SD-higher WHR in a codominant fashion. When WHR was additionally corrected for BMI, thus providing a measure of body fat distribution throughout the range of BMI, there remained significant evidence for association with both markers that was of similar magnitude and statistical significance. There was no association between genotype at any polymorphism and BMI or plasma leptin level. These data show that genetic variants at the POMC locus influence body fat distribution within the normal range, suggesting a novel role for POMC in metabolic regulation.